Effects of preparation methods for V2O5-TiO2 aerogel catalysts on the selective catalytic reduction of NO with NH3 - Kang, Min; Choi, Jinsoon; Kim, Yong Tae; Park, Eun Duck; Shin, Chee Burm; Suh, Dong Jin; Yie, Jae Eui (KOREAN INST CHEM ENGINEERS+, 2009)
A series of V2O5-TiO2 aerogel catalysts were prepared by the sol-gel method with subsequent supercritical drying with CO2. The main variables in the sol-gel method were the amounts of V2O5 and when the vanadium precursor was introduced. V2O5-TiO2 xerogel and V2O5/TiO2 (P-25) were also prepared for comparison. The V2O5-TiO2 aerogel catalysts showed much higher surface areas and total pore volumes than V2O5-TiO2 xerogel and impregnated V2O5/TiO2 (P-25) catalysts. The catalysts were characterized by N-2 physisorption, X-ray diffraction (XRD), FT-Raman spectroscopy, temperature-programmed reduction with H-2 (H-2-TPR), and temperature-programmed desorption of ammonia (NH3-TPD). The selective catalytic reduction of NOx with ammonia in the presence of excess O-2 was studied over these catalysts. Among various V2O5-TiO2 catalysts, V2O5 supported on aerogel TiO2 showed a wide temperature window exhibiting high NOx conversions. This superior catalytic activity is closely related to the large amounts of strong acidic sites as well as the surface vanadium species with characteristics such as easy reducibility and monomeric and polymeric vanadia surface species.
Keywords: MORPHOLOGICAL PROPERTIES; TITANIA AEROGELS; AMMONIA; BEHAVIOR; OXIDE